2013
DOI: 10.1177/0961203313477223
|View full text |Cite
|
Sign up to set email alerts
|

Hearing and vestibular disorders in patients with systemic lupus erythematosus

Abstract: Migraine, SNHL and episodic vertigo are comorbid conditions in patients with SLE, but migraine is not associated with SNHL or vertigo in these patients. However, SNHL and vertigo are associated conditions in SLE, suggesting a common audiovestibular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…The vestibular system could be involved in SLE, but vertigo and dizziness have rarely been reported [35, 36]. Balance disorders as a consequence of SLE have been observed also in children [37]; however, the incidence of vestibular symptoms may be underestimated due to their slowly progressive onset and consequent compensation by the somatosensory system and vision.…”
Section: Inner Ear Involvement In Autoimmune Diseasesmentioning
confidence: 99%
“…The vestibular system could be involved in SLE, but vertigo and dizziness have rarely been reported [35, 36]. Balance disorders as a consequence of SLE have been observed also in children [37]; however, the incidence of vestibular symptoms may be underestimated due to their slowly progressive onset and consequent compensation by the somatosensory system and vision.…”
Section: Inner Ear Involvement In Autoimmune Diseasesmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE), a chronic inflammatory autoimmune disease, affects numerous organs and systems, including the skin, joints, lungs, and kidneys. Ear findings are not included in the diagnostic criteria, but SLE is associated with sensorineural hearing loss, tinnitus, and vestibular disorders (1,2). Vestibular symptoms are common in patients with SLE: one questionnaire-based study found that their frequency of audiovestibular symptoms, including vertigo, was significantly higher than in healthy control patients (3,4).…”
Section: Resultsmentioning
confidence: 99%
“…However, sensorineural hearing loss and tinnitus are associated with SLE (2). Inner ear dysfunction is frequently detected in both adult and pediatric SLE patients (35).…”
Section: Introductionmentioning
confidence: 99%